Teachers’ cognition in changing practice: Implementing group discussion in EFL classes in universities in South-Western China - Murray, Neil; Liddicoat, Anthony John; Zhen, Fengchao (American Journal of Education and Learning, 2024)
This paper presents a qualitative study that examined how group discussions were used in EFL classes at universities in Yunnan Province, a resource-limited region in southwest China and how regional issues affected their use and effectiveness. It focuses, in particular, on the role of pedagogical knowledge and pedagogical reasoning in implementing group discussion in tertiary-level English classes. The data was collected through a combination of classroom observations and interviews with a group of teachers who had recently completed an extensive professional development program and were seeking to bring about change in their practice after attending the workshop. The findings indicate that although most teachers understood the importance of group discussion to students’ learning and to respond to the new English language curriculum’s emphasis on developing their communicative competence, they did not necessarily have the pedagogical knowledge and reasoning needed to implement group discussion tasks effectively or to respond to the challenges attempts to do so presented within their institutional cultures. These findings emphasize the need for in-service and pre-service language teacher development programmes that enhance teachers’ knowledge of theory, their appreciation of its practical relevance, and their ability to apply that knowledge in their pedagogical decision-making.